Relationship between social support, anxiety, and depression among frontline healthcare workers in China during COVID-19 pandemic - Zhan, Jie; Chen, Chen; Yan, Xiaoting; Wei, Xiaojing; Zhan, Lechang; Chen, Hongxia; Lu, Liming (Frontiers in Psychiatry, 2022)
Background Social support is an important factor affecting individual mental health. However, the relationship between social support and mental health in frontline healthcare workers (FHW) during the coronavirus disease 2019 (COVID-19) pandemic has garnered less attention. In this study, we aimed to investigate the level of social support and the prevalence of depression and anxiety in FHW during the COVID-19 pandemic and determine the factors affecting the relationship between social support, depression, and anxiety. Methods A cross-sectional study using an online survey was conducted to collect data from FHW between 15 February and 31 March 2020 in China. The data included demographic factors, Self-rated Depression Scale (SDS), Self-rated Anxiety Scale (SAS), and Social Support Rate Scale (SSRS). Spearman correlation test was performed to determine the correlation among SAS, SDS, and SSRS scores. Multiple linear regression analysis was performed to determine the relationship among demographic factors, social support, depression, and anxiety in FHW. Results Of all 201 participants, 44 (21.9%) had depressive symptoms and 32 (15.9%) had anxiety symptoms. The average total SSRS scores among FHW were lower than that of the norms of the Chinese general population (37.17 ± 7.54 versus 44.38 ± 8.38, P < 0.001). Marital status positively affected the SSRS score (β = 7.395, P < 0.01). Age over 40 years old negatively affected the SSRS score (β = −5.349, P = 0.017). The total SSRS score, subjective social support score, objective social support score, and support utilization score among FHW negatively correlated with the SAS score and SDS score (P < 0.05). A lower support utilization score was significantly associated with high anxiety and depressive symptoms (β = −0.869, P = 0.024; β = −1.088, P = 0.035, respectively). Conclusion During the COVID-19 pandemic, FHW experienced depression, anxiety, and inadequate social support. The marital status and age had a major impact on social support. Social support was inversely associated with depression and anxiety. Improving the mental health of FHW by strengthening social support is crucial. Future studies are needed to investigate how to improve the level of social support and mental health condition of FHW facing public health emergencies in the future.